Kitāb al-waḥshiyyāt : Nuskha bar gardān bih qaṭʿ-i aṣl-i nuskha-yi khaṭṭi-yi kitābkhāna-yi shakhṣi-yi Dr. Waḥīd Dhulfiqārī kitābat 550 H - Tammām, Abū (Miras Maktoob, ISBN: 9789004365452., 2019)
The Arab poet and anthologist Abū Tammām (d. 231/845) was born in Jāsim in Syria, between Damascus and Darʿā. After a first period as a weavers' assistant in Damascus and as a water-seller in Cairo, studying poetry on the side, he had his breakthough as a poet after his return to Syria in the time of al-Muʿtaṣim billāh (r. 218-27/833-42). Considered as the greatest panegyrist of his time, he sang the praises of the caliph and many other public figures of his age. Besides Egypt, Abū Tammām also travelled to other regions, his most celebrated sojourn being in Hamadan where he compiled his famous poetic anthology the Kitāb al-ḥamāsa . The present work is a similar compilation by him, though smaller and much less known. Edited previously on the basis of one manuscript from Istanbul, the present facsimile edition is of a second manuscript, this time from Yazd. Some folios missing but good readings, interesting marginalia.